A Note on Symmetric Properties of the Twisted q-Bernoulli Polynomials and the Twisted Generalized q-Bernoulli Polynomials. (24th June 2010) - Jang, L.-C.; Yi, H.; Shivashankara, K.; Kim, T.; Kim, Y. H.; Lee, B.
Abstract : We define the twistedq -Bernoulli polynomials and the twisted generalizedq -Bernoulli polynomials attached toχ of higher order and investigate some symmetric properties of them. Furthermore, using these symmetric properties of them, we can obtain some relationships between twistedq -Bernoulli numbers and polynomials and between twisted generalizedq -Bernoulli numbers and polynomials.